Noninvasive oxygenation and ventilation strategies for viral acute respiratory failure: a comprehensive systematic review and meta-analysis - Fredy Leonardo Carreño-Hernández; Sergio Prieto; Daniela Abondando; Jairo Alejandro Gaitán; Yenny Rocío Cárdenas -Bolívar; Adriana Beltrán; Jorge Iván Alvarado-Sánchez; Joseph L. Nates (Systematic Reviews)
Abstract Background The COVID-19 pandemic has resulted in a critical shortage of respiratory ventilators, highlighting the urgent need to explore alternative treatment options for patients with acute respiratory distress syndrome (ARDS) caused by respiratory viruses, as an alternative to invasive mechanical ventilation (IMV) in future pandemics. Objectives The objective of this study was to assess the effectiveness of alternative noninvasive oxygenation and ventilation strategies in comparison to invasive mechanical ventilation (IMV) in patients with virus-induced acute respiratory failure (ARF). The primary outcome was the all-cause ICU mortality rate. Methods A systematic review was conducted following the Cochrane guidelines and PRISMA reporting guidelines. The search encompassed databases such as Medline, Cochrane CENTRAL, and Embase to identify relevant indexed literature. Additionally, gray literature was included by consulting regulatory agencies. The included studies compared various oxygenation and ventilatory alternatives, such as high-flow nasal cannula (HFNC), continuous positive airway pressure (CPAP), or noninvasive mechanical ventilation (NIMV) with IMV. An exploratory meta-analysis was performed by calculating the risk ratio (RR) by random effects and meta-regression to explore possible sources of heterogeneity and to compare ventilatory alternatives against IMV to reduce mortality, length of stay (LOS) days in ICU, nosocomial infection, and barotrauma. Results A total of forty-seven studies were included in this systematic review. NIMV had an RR of 0.70 (0.58–0.85), HFNC had an RR of 0.54 (0.42–0.71), and CPAP had an RR of 0.80 (0.71–0.90), with meta-regression models that reduced heterogeneity to 0%. For LOS days in ICU, NIMV had 0.38 (− 0.69: − 0.08) lower days and HFNC 0.29 (− 0.64: 0.06) lower days with meta-regression models that reduction heterogeneity to 0% for HFNC and 50% for NIMV. Not enough studies reported nosocomial infection or barotrauma to evaluate them in a meta-analysis. The overall quality of evidence, as assessed by GRADE evaluation, was determined to be from very low to medium certainty depending on the ventilatory strategy and outcome. Conclusions The findings of this systematic review support the use of alternative noninvasive oxygenation and ventilation strategies as viable alternatives to conventional respiratory ventilation for managing viral-induced ARF. Although it is essential to interpret these findings with caution given the overall low to medium certainty of the evidence, the integration of these modalities as part of the management strategies of these patients could help reduce the utilization of ICU beds, invasive ventilators, and costs in both developed and developing countries.